Annual Plan 2005-06 Revised Outlay 2005-06 - Planning Commission (Planning Commission, 2005)
I am directed to refer to the Government of Andhra Pradesh’s letter No. 7122/PLG..XVIII/04, 06.03.2006 on the above subject and to convey the acceptance of Planning Commission to the revised outlay of Rs.13530.47 crores subject to availability of resources. The revised scheme of financing the revised outlays, is given at Annexure-I. A statement showing the distribution of revised Plan outlay under different heads and subheads of development is enclosed. the earmarked outlays for different schemes have also been indicated therein. Kindly acknowledge the receipt of this letter.
Planning Commission State Plan Division